Learning to think : child development in social context 2 - Light, Paul.; Sue, Sheldon; Woodhead, Martin (USA : Routledge, 1991)
Concentrating on the development of infants, this book emphasizes the growing concern with naturalistic observations of everyday life. Analysis of such observations can improve the understanding of the relation between the behaviour of the caregiver and the emerging competencies of the child.
Includes bibliographical references and index.
Keywords: Child development; Child psychology -- Cross-cultural studies; Child psychology